2013
DOI: 10.1093/mnras/stt1830
|View full text |Cite
|
Sign up to set email alerts
|

Merging tree algorithm of growing voids in self-similar and CDM models

Abstract: Observational studies show that voids are prominent features of the large scale structure of the present day Universe. Even though their emerging from the primordial density perturbations and evolutionary patterns differ from dark matter halos, N -body simulations and theoretical models have shown that voids also merge together to form large void structures. In this study, following Sheth & van de Weygaert (2004), we formulate an analytical approximate description of the hierarchical void evolution of growing … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 83 publications
(148 reference statements)
1
4
0
Order By: Relevance
“…This indicates that the size distributions of HOD Sparse and the N-body Mock sub-sample tends to have larger voids compared to the voids in HOD Dense due to their low density environment. This result agrees with Watson et al (2014); Jennings et al (2013); Russell (2013Russell ( , 2014. On the other hand, as aforementioned, the N-body Mock catalog has higher redshift z = 0.53 than the two other samples, therefore N-body Mock sample may imply larger size voids at z = 0 compared to HOD Sparse.…”
Section: Conclusion and Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…This indicates that the size distributions of HOD Sparse and the N-body Mock sub-sample tends to have larger voids compared to the voids in HOD Dense due to their low density environment. This result agrees with Watson et al (2014); Jennings et al (2013); Russell (2013Russell ( , 2014. On the other hand, as aforementioned, the N-body Mock catalog has higher redshift z = 0.53 than the two other samples, therefore N-body Mock sample may imply larger size voids at z = 0 compared to HOD Sparse.…”
Section: Conclusion and Discussionsupporting
confidence: 86%
“…Today we know that voids dominate the total observed volume of the large scale structure (Kirshner et al 1981;Geller & Huchra 1989;da Costa et al 1994;Shectman et al 1996) and they are very sensitive to their environments which can strongly affect their shape as well their distributions (Sheth & van de Weygaert 2004;Russell 2013Russell , 2014. Therefore the void size distribution functions may play an important role to understand the dynamical processes affecting the structure formation of the Universe (Croton et al 2005;Goldberg & Vogeley 2004;Hoyle et al 2005).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus the void destruction rate does not play a significant role in the late-time evolution of voids, and can be ignored in theoretical treatments. Additionally, as pointed out by Russell (2013), the collapsing process is completely negligible for all but the smallest voids, although this result is in conflict with analyses based on the adhesion approximation (Sahni et al 1994).…”
Section: Discussionmentioning
confidence: 77%
“…This fact has been known since early studies that showed voids are integral features of the Universe (Chincarini & Rood 1975;Gregory & Thompson 1978;Einasto et al 1980;Weygaert & Platen 2011). Sheth & van de Weygaert (2004); Russell (2013Russell ( , 2014 show that the distribution of voids can be affected by their environments. As a result, the void size distribution may play a crucial role to understand the dynamical processes affecting the structure formation of the Universe (Croton et al 2005;Goldberg & Vogeley 2004;Hoyle et al 2005).…”
Section: Introductionmentioning
confidence: 91%